THE INFLUENCE OF PRODUCT ASSORTMENT AND PRICE DISCOUNT IN ONLINE MARKETPLACE TOWARD CONSUMER PURCHASE DECISION OF GENERATION Z IN MANADO - Bee, Sharon C.; Worang, Frederik G.; Wangke, Shinta (Universitas Sam Ratulangi, 2022)
In this 4.0 era, many aspects of people's lifestyles nowadays are greatly helped through both information and communication technology, which is the Internet. Thus, online media has become an alternative for people to carry out their activities, for example is shopping. Currently, the E-Commerce platform that is in great demand in shopping is the Online Marketplace. Online Marketplace is a buying and selling platform that acts as an intermediary between sellers and buyers that provides sales features and secure payment facilities. Therefore, Online Marketplace has become the most widely used platform, especially among Generation Z. Currently, every Online Marketplaceâ€™s company is competing to promote their platform in order to increase the number of users and also increase sales by using marketing strategy. Therefore, the researcher wants to find out the marketing strategy from the perspective of the consumers. The researcher assumes, there are two marketing strategies that can be implemented, such as Product Assortment and Discounts, which can attract customers to make purchasing decisions. This research has been completed by researcher using a quantitative method, by distributing questionnaires to 100 Generation Z as respondents in Manado. Let the results of this research have a positive influence on Generation Z in Manado, especially to help online marketers in developing their products and the prices to be offered.Â Keywords: product assortment, price discount, consumer purchase decision